The Niger Delta and Human Rights in Nigeria - Emmanuel O, Davies (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2010)
The Niger Delta Region in the enclave called Nigeria today has been terribly locked in an endless battle for its Human Rights which also includes the right to development and economic autonomy, with various predatory institutions which have across time, relentlessly sought to command its immense natural wealth and dictate to it the terms and manner of development it must follow. The world conference on Human Rights held in Vienna, Austria recognized the fact that development rights are arguably fundamental and inalienable rights. The recognition of the right to development and the meeting of basic economic and social needs as part of fundamental human rights by the conference marked a turning point in the United Nations recognition of only Civil rights as fundamental human rights.This paper takes a look at the Niger Delta , its problems of human rights to which development rights is a part and contends that the Niger Delta development rights must be promoted and defended at all cost on the basis of proper understanding of the institutionalization of a transparent and genuine democracy. KeyWords:*Niger Delta, *human rights, *development, *resource control, *Nigeria, *fundamental rights, *linternational law